Biocementation Influence on Flexural Strength and Chloride Ingress by Lysinibacillus sphaericus and Bacillus megaterium in Mortar Structures - Daniel Karanja Mutitu; Jackson Muthengia Wachira; Romano Mwirichia; Joseph Karanja Thiong’o; Onesmus Mulwa Munyao; Muriithi Genson (Journal of Chemistry)
The concrete/mortar durability performance depends mainly on the environmental conditions, the microstructures, and its chemistry. Cement structures are subject to deterioration by the ingress of aggressive media. This study focused on the effects of Bacillus megaterium and Lysinibacillus sphaericus on flexural strength and chloride ingress in mortar prisms. Microbial solutions with a concentration of 1.0 × 107 cells/ml were mixed with ordinary Portland cement (OPC 42.5 N) to make mortar prisms at a water/cement ratio of 0.5. Four mortar categories were obtained from each bacterium based on mix and curing solution. Mortar prisms of 160 mm × 40 mm × 40 mm were used in this study. Flexural strength across all mortar categories was determined at the 14th, 28th, and 56th day of curing. Mortars prepared and cured using bacterial solution across all curing ages exhibited the highest flexural strength as well as the highest percent flexural strength gain. Lysinibacillus sphaericus mortars across all mortar categories showed higher flexural strength and percent flexural strength gain than Bacillus megaterium mortars. The highest percent flexural strength gain of 33.3% and 37.0% was exhibited by the 28th and 56th day of curing, respectively. The mortars were subjected to laboratory prepared 3.5% by mass of sodium chloride solution under the accelerated ion migration test method for thirty-six hours using a 12 V Direct Current power source after their 28th day of curing. After subjecting the mortar cubes to Cl media, their core powder was analyzed for Cl content. From these results, the apparent diffusion coefficient, Dapp, was approximated from solutions to Fick’s 2nd Law using the error function. Bacillus megaterium mortars across all mortar categories showed lower apparent diffusion coefficient values with the lowest being 2.6456 × 10–10 while the highest value for Lysinibacillus sphaericus mortars was 2.8005 × 10–10. Both of the test bacteria lowered the ordinary Portland cement Cl-ingress but Bacillus megaterium was significantly more effective than Lysinibacillus sphaericus in inhibition.